2019
DOI: 10.1038/s41598-019-54908-2
|View full text |Cite
|
Sign up to set email alerts
|

Introgression of Sub1 (SUB1) QTL in mega rice cultivars increases ethylene production to the detriment of grain- filling under stagnant flooding

Abstract: In the recent time, Submergence1 (Sub1)QTL, responsible for imparting tolerance to flash flooding, has been introduced in many rice cultivars, but resilience of the QTL to stagnant flooding (SF) is not known. The response of Sub1-introgression has been tested on physiology, molecular biology and yield of two popular rice cultivars (Swarna and Savitri) by comparison of the parental and Sub1-introgression lines (SwarnaSub1 and SavitriSub1) under SF. Compared to control condition SF reduced grain yield and tiller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 60 publications
(94 reference statements)
0
24
0
Order By: Relevance
“…Some studies showed that cytokinin is involved in regulating grain production [ 41 , 42 ]. Other plant hormones, including BR, ET, JA, and SA, also play a crucial role in seed development and grain production [ 5 , 17 , 18 , 43 , 44 , 45 ]. In this study, we observed that many differentially expressed genes were related to plant hormone biosynthesis and/or signaling pathways; these genes included PYLs (abscisic acid receptor), ABI5 (ABSCISIC ACID-INSENSITIVE 5), PP2C (probable protein phosphatase 2C), SAPKs (serine/threonine-protein kinase), SAURs (auxin-responsive protein), JAR (jasmonic acid-amido synthetase), EIN2 (ETHYLENE-INSENSITIVE 2), and TIFY ( Table S2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies showed that cytokinin is involved in regulating grain production [ 41 , 42 ]. Other plant hormones, including BR, ET, JA, and SA, also play a crucial role in seed development and grain production [ 5 , 17 , 18 , 43 , 44 , 45 ]. In this study, we observed that many differentially expressed genes were related to plant hormone biosynthesis and/or signaling pathways; these genes included PYLs (abscisic acid receptor), ABI5 (ABSCISIC ACID-INSENSITIVE 5), PP2C (probable protein phosphatase 2C), SAPKs (serine/threonine-protein kinase), SAURs (auxin-responsive protein), JAR (jasmonic acid-amido synthetase), EIN2 (ETHYLENE-INSENSITIVE 2), and TIFY ( Table S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The change in plant hormone levels could also affect the grain filling process in plants. Increasing ethylene levels in developing seeds inhibits the accumulation and activities of starch synthesis-related enzymes, and further inhibits the biosynthesis of carbohydrates in the developing spikelets and decreases the grain-filling rate [ 5 , 6 ]. Abscisic acid (ABA) also regulates the sink activity during grain filling [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…6c). In particular, the expression at anthesis (day 0) was higher in the former compared to the latter, when ethylene production culminates in rice spikelets resulting grain morbidity 7,13,16 irrespective of cultivar difference 44 . In comparison, the situation was just opposite for miRNAs with targets on IAA pathway (Fig.…”
Section: Genes Targeted By Differentially Expressed Mirnasmentioning
confidence: 93%
“…These miRNAs had Os11t0141000-02 and Os07t0239400-01 (PP2A regulatory subunit-like protein and ethylene-responsive small GTP-binding proteins) as targets with highest probability. Irrespective of cultivar difference, ethylene production climaxes at anthesis 44 and in all probability, these miRNA participated in the process of ethylene biosynthesis for both high and low sterile cultivars used. Further, our study identified expression of MIR396h on day 5 post anthesis, that had multiple targets, such as, Os02t0776900-01, a transcription activator involved in gibberellin induced stem elongation, Os01t0643300-02, an auxin efflux carrier protein and Os01t0643300-01, a PIN1-like auxin transport protein with maximum probability.…”
Section: Genes Targeted By Differentially Expressed Mirnasmentioning
confidence: 96%
“…Kuanar et al . [ 186 ], investigated the response of Sub1 incorporation into high yielding rice cultivars by comparing the Sub1 incorporated and parental lines of ‘Swarna’ and ‘Savitri’ under stagnant flooding condition. They reported that the Sub 1 incorporation in to the mega cultivars increase sensitivity to stagnant flooding.…”
Section: Marker-assisted Breeding Approaches For the Development Of Flooding Tolerance In Ricementioning
confidence: 99%